2021
DOI: 10.1111/febs.16133
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signaling in cancer progression and therapy

Abstract: VGCCs voltage-gated calcium channels SOCE store-operated calcium entry CRAC calcium release-activated Ca 2+ TRP Transient receptor potential ER endoplasmic reticulum SR sarcoplasmic reticulum IP3 inositol 1,4,5-trisphosphate GPCRs G-protein-coupled receptors MCU mitochondrial calcium uniporter CaMKII Ca 2+ -calmodulin-dependent protein kinase II CACNA1E calcium voltage-gated channel subunit alpha1 E CCBs calcium channel blockers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 216 publications
(250 reference statements)
0
33
0
Order By: Relevance
“…Changes in intracellular Ca 2+ concentration are affected by the influx of extracellular Ca 2+ and the release of ca 2+ from intracellular ca 2+ stores, such as the ER, mitochondria and lysosomes. When cells are excited by external stimuli, various Ca 2+ channels are opened or closed, which results in the dysregulation of ca 2+ homeostasis (22,23). Previous studies have reported that the Ca 2+ signaling pathway is a key regulator of nutrient uptake, metabolism and utilization (24,25).…”
Section: Physiological Role Of Ca 2+ In the Livermentioning
confidence: 99%
“…Changes in intracellular Ca 2+ concentration are affected by the influx of extracellular Ca 2+ and the release of ca 2+ from intracellular ca 2+ stores, such as the ER, mitochondria and lysosomes. When cells are excited by external stimuli, various Ca 2+ channels are opened or closed, which results in the dysregulation of ca 2+ homeostasis (22,23). Previous studies have reported that the Ca 2+ signaling pathway is a key regulator of nutrient uptake, metabolism and utilization (24,25).…”
Section: Physiological Role Of Ca 2+ In the Livermentioning
confidence: 99%
“…However, cellular Ca 2+ signaling proteomes, such as Ca 2+ channels, and Ca 2+ -binding proteins including calmodulin (CaM) and Ca 2+ -sensing receptor (CaSR), are tissue-specific and produce distinct Ca 2+ signals suitable for tissue physiology [ 13 ]. Cytosolic Ca 2+ signals practically participate in every aspect of cellular life, and rigorous regulation of Ca 2+ homeostasis is important for preventing dysfunctions that lead to pathological changes [ 14 ]. In a pathological environment, remodeling of Ca 2+ flux contributes to processes important for cancer progressions, such as uncontrolled proliferation, invasiveness of tumor cells, and the development of resistance to cancer therapies [ 15 ].…”
Section: Ca 2+mentioning
confidence: 99%
“…Ion channels are versatile regulators of several physiological and pathophysiological mechanisms, including cancer-relevant processes such as tumor progression, apoptosis inhibition, proliferation, migration, invasion, and chemoresistance. The calcium signaling pathway, the fourth enriched pathway in JIMT-1 cells, can precisely regulate many master regulators in cancer via the opening of plasmalemmal calcium channels in response to various stimuli leading to localized high levels of Ca2+, which subsequently influences gene expression (Wu et al, 2021). Ion channels are the key regulators of cellular functions, conducting ions selectively through a pore-forming structure located in the plasma membrane, protein-protein interactions being one of their main regulatory mechanisms.…”
Section: Integration Of Dna Methylation and Gene Expression Datamentioning
confidence: 99%